Direct and indirect costs of parasitism preceding a population decline of an Arctic ungulate - Dickinson, Eleanor R.; Nwafor-Okoli, Chinyere; Checkley, Sylvia L.; Elkin, Brett; Branigan, Marsha; Serrano Ferron, Emmanuel; Kutz, Susan J. (2024)
Parasites negatively affect the fitness of ungulate hosts directly, and in wild ungulates, these effects may be synzootic with other stressors, such as limited nutritional resources. In the Arctic, muskoxen (Ovibos moschatus) occur in a highly seasonal environment and must rely on finite energetic resources for survival and productivity. We investigated the costs of gastrointestinal nematodes on the body condition and reproductive status of 141 muskoxen, on Banks Island, Canada, when the population was at a peak in numbers and density. Using a Partial Least Squares Path Modelling approach, we found that high adult nematode abundance was associated with lower body condition, and high parasite abundance was associated with female reproduction including the indirect effect through on body condition (n = 87). These findings suggest that individuals prioritize energetic reserves for reproduction over parasite defence. In fall 2003, a severe icing event that restricted access to forage was associated with high overwinter mortality of muskoxen and a population crash. Through direct and indirect costs of parasite infection on body condition and reproduction, the high abundance of parasites may have contributed to the effects of this extreme weather event. Understanding the mechanisms in which parasites impact fitness can help explain the ecological drivers of ungulate populations and predict the interactions between the environment and populations.